DESAIN PROGRAM INTERVENSI TERAPI THERAPLAY UNTUK MENINGKATKAN KEMAMPUAN ANAK AUTIS DALAM INITIATING JOINT ATTENTION - Hanoum, Magdalena (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
The purpose of Theraplay is to develop and increase parents and child relationship. Along with the progress of relationship between parents and child, social interaction ability of children will increase through structured and playfulness activity that they do with their parents. While they are playing  together, they are also sharing some joint attention one and another to focus on their activity. Through it, autism children are stimulated to develop their ability in responding and initiating joint attention. Research design is pre-eliminiary research, and the purpose are to collect initial data from beginning survey, observation and interviewing to autism children family, assessment of their basic need and to make a design of  intervention program using theraplay. The beginning survey and early assessment explain that  autism children with high intellectual functioning ages 8-9 years old, can make responding joint attention (RJA) consistently but their ability to make initiating joint attention (IJA) is not consistent. So that, the purpose of  Theraplay intervention program in this research is to enhanced initiating joint attention (IJA) ability of autism children